Demonstration of early efficacy results of the delayed-release combination of doxylamine-pyridoxine for the treatment of nausea and vomiting of pregnancy. Issue 1 (December 2016) - Koren, Gideon; Clark, Shannon; Hankins, Gary; Caritis, Steve; Umans, Jason; Miodovnik, Menachem; Mattison, Donald; Matok, Ilan
Abstract Background Nausea and vomiting of pregnancy (NVP) affects up to 80% of expecting mothers. In April 2013 the FDA approved the delayed-release combination of doxylamine succinate and pyridoxine hydrochloride (Diclegis®) for NVP, based in part, on the results of a phase III randomized trial demonstrating the efficacy of this drug combination [study drug marketed under the trade name Diclectin® in Canada and Diclegis® in the United States] compared to placebo in pregnant women. Study drug dosing occurred for 14 days, which is substantially longer than what has been performed in similar studies. The objective of this study was to evaluate, through secondary analysis, whether the primary measure of efficacy can be demonstrated after five days of treatment. Methods Women suffering from NVP were randomized to receive Diclegis® (n  = 131) or placebo (n  = 125) for 14 days at doses ranging from two to four tablets a day, based on a pre-specified titration protocol. The primary efficacy endpoint was the change in the validated Pregnancy-Unique Quantification of Emesis (PUQE) score at baseline versus Day 15 between Diclegis®-treated and placebo-treated women. For the present study, the change in PUQE score between baseline and Day 15 (end of the study) was compared to the changes observed for Days 3, 4, and 5. Results The use of delayed-release doxylamine succinate and pyridoxine hydrochloride tablets show improved NVP symptom control as compared to placebo on Days 3, 4 and 5, with sustained efficacy until the end of the trial. Conclusion A four day study drug dosing trial with Diclegis® is sufficient to document efficacy, as the results are similar to those achieved after 14 study drug dosing days. The benefit seen at the earlier time validates drug efficacy and minimizes the natural course of improvement. Trial registration CTR No. NCT006 14445 2007.